Contribution to the Improvement of Vegetative Propagation by Greenhouse Cuttings of Odorous Verbena (Aloysia citrodora) - Hamza, El Finou; Issam, El-Khadir; Driss, Hmouni (Talenta Publisher, 2021)
Currently several species are threatened with extinction due to climatic factors, population pressure and the strong global demand for a continuous and uniform supply of fragrant, aromatic and medicinal plants. The multiplication and domestication of these species remains the only way to save them from extinction, our study is within the framework of propagation by cuttings of odorous verbena (Aloysia citrodora). In fact, some parameters influencing the success of cuttings have been studied, namely the nature of the substrate, the effect of certain rooting products and the position of the cutting in relation to the mother plant (basal or apical), the tests were carried out in a tunnel greenhouse at the ibn tofail university, faculty of sciences kenitra, Morroco. Out of 144 trials, the success rate of cuttings according to the type of substrate was 91.66%, 75% and 83.33% respectively for substrates S1 (soil only), S2 (1/2 sand and 1/2 compost) and S3 (1/3 soil; 1/3 compost and 1/3 peat). For the three products, we didn’t make combinations. but we followed the effect of each product alone, For the treatment effect, 77%, 0% and 69% respectively were obtained for Product 1 (auxin), Product 2 (based on mineral matter and amino acids) and Product 3 (seaweed extract). With regard to the position of the cutting, high percentages were obtained for cuttings from the basal position.